Assessing Teachers’ Knowledge of How to Use Computer Programming in Science and Technology Education - Karlsen, Niklas; Henriksen, Ellen Karoline; Pajchel, Katarina (Journal of science education and technology, 2025)
Programming and computational thinking have been introduced into the curricula of several countries, also in relation to science and technology education. Preparing pre-service teachers for using programming in science education is therefore an important and relevant task. The purpose of this article is to describe what knowledge may be relevant for teachers who are to use programming in science and technology education and to propose a questionnaire to aid in assessing this knowledge. The proposed questionnaire can be used for tracking development over time and for identifying areas where teachers need more knowledge.